PENGARUH AKSESIBILITAS PEMBIAYAAN TERHADAP PENDAPATAN PETANI KOPI DI LEMBAH GUMANTI, KABUPATEN SOLOK - Cindy Paloma; Yusmarni Yusmarni; Ami Sukma Utami; Hasnah Hasnah (Jurnal Agrisep)
Capital is one of the most important factors for increasing coffee production. Coffee farmers accessibility to resources financing is still limited. Farmers are considered not bankable by financial institutions.This condition hampering them to manage and develope coffee farm. This study aims to : 1) analyze the characteristics of coffee farmer in the Lembah Gumanti District , 2) analyze factors that influence coffee farmers income in Lembah Gumanti District. The study was conducted in Solok Regency which is the largest coffee production in West Sumatra. This study using 30 samples of coffee farmers selected by simple random sampling method. Descriptive analysis and multiple regression analysis are used to answer the research question. Based on the results of descriptive analysis, the characteristics of coffee farmers is: farmer who in productive age with a low level of education, have family members ranged from 2-6 people, 90% of coffee farmer have experience under 5 years, 93% of coffe farmer capital comes from own capital and 3% of coffe farmer capital from loan. Based on the multiple regression output, access to financial institutions , labor, farming experience, age, education, productivity, cost of farming, capital source, coffee bean prices and plants age variabels, simultaneously affected and significant to coffee farmers income. In Partial test, labor, number of trees, cost of farming and source of capital have a significant effect on coffee farmer income. The labor factor, the number of trees and the source of capital have a positive effect while the cost of farming has a negative effect. Farmer access to financial institutions is negative and not significant to income, because 63% of coffee farmers dont have access to financial institutions, and 36% of farmers who have access to financial institutions not using loan funds for farming, but for other needs, such as household consumption.